The effectiveness of the Missouri Mathematics Project learning model on high school students' mathematical problem-solving skills and math anxiety levels - Nadia Mei Safitri; Karim Karim; Kamaliyah Kamaliyah; Nasrudeen Ayinde Malik (Universitas Sarjanawiyata Tamansiswa, 2026)
Mathematical problem-solving skills are one of the important competencies that students must have in mathematics learning. However, in reality, these skills are still relatively low, while math anxiety often arises and has the potential to hinder the learning process of students. Therefore, a learning model is needed that can improve mathematical problem-solving skills while paying attention to the affective aspects of students. This study aims to analyze the effectiveness of the Missouri Mathematics Project (MMP) learning model on high school students' mathematical problem-solving skills and levels of math anxiety. This study uses a pretest-posttest control group design. The research subjects were 10th grade students at State High School 1 Banjarmasin in the 2025/2026 academic year. The research instruments were a mathematical problem-solving ability test and a math anxiety questionnaire. The data were analyzed using descriptive and inferential statistics. The results showed that the mathematical problem-solving abilities of students taught using the MMP model were better than those of students taught using the conventional learning model. Meanwhile, the level of math anxiety among students in the MMP class was not significantly different from that in the conventional class. Thus, the MMP learning model is effective in improving students' mathematical problem-solving abilities, but has not yet shown its effectiveness in reducing students' math anxiety. This study contributes to mathematics education by providing empirical evidence that the Missouri Mathematics Project learning model can be used as an alternative instructional strategy to strengthen students' mathematical problem-solving skills, although additional approaches are still needed to address students' math anxiety.